REGIONAL ENGAGEMENT OF THE HIGHER EDUCATION INSTITUTIONS IN THE REPUBLIC OF CROATIA (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
The aim of this paper is to present results of empirical research on regional orientation and engagement of Croatian higher education institutions (HEIs). The second goal is to research if there is any difference between Croatian universities and polytechnics in their regional focus. Contribution to regional economic, social and cultural development of a region is a recent mission that is, in addition to education and research, imposed on HEIs. With the establishment of public polytechnics across the country, the Republic of Croatia has adopted a new mission of HEIs, and has established them with the aim of contributing to regional development. Such institutions should, in comparison to universities, be more regionally oriented, i.e. offer study programs and research needed by the regional industry. Since the differences between universities and vocational studies are not clearly defined by the law in Croatia, referred orientation should be a component of distinction. For the purposes of this paper, a sample of Croatian public university constituents and polytechnics was defined. A questionnaire was drafted and sent to the relevant persons at the HEIs. Research results and statistical tests indicate that there is no statistically significant difference in regional orientation and engagement between universities and polytechnics. Further research in this area will seek to contribute to raising awareness of the HEIs and of the economic policy carriers regarding the differentiation of the HEIs and to encourage the implementation of the regional mission of Croatian polytechnics, particularly through external evaluation.Keywords: Universities, polytechnics, differences, regional engagement, the Republic of Croatia